A role of gut microbiota metabolites in HLA-E and NKG2 blockage immunotherapy against tumors: new insights for clinical application - Cheng, Wenyue; Zhu, Ningning; Wang, Juanjuan; Yang, Rongcun (Frontiers in Immunology, 2024)
One of major breakthroughs in immunotherapy against tumor is from blocking immune checkpoint molecules on tumor and reactive T cells. The development of CTLA-4 and PD-1 blockage antibodies has triggered to search for additional effective therapeutic strategies. This causes recent findings that blocking the interaction of checkpoint molecule NKG2A in NK and CD8 T cells with HLA-E in tumors is effective in defensing tumors. Interestingly, gut microbiota also affects this immune checkpoint immunotherapy against tumor. Gut microbiota such as bacteria can contribute to the regulation of host immune response and homeostasis. They not only promote the differentiation and function of immunosuppressive cells but also the inflammatory cells through the metabolites such as tryptophan (Trp) and bile acid (BA) metabolites as well as short chain fatty acids (SCFAs). These gut microbiota metabolites (GMMs) educated immune cells can affect the differentiation and function of effective CD8 and NK cells. Notably, these metabolites also directly affect the activity of CD8 and NK cells. Furthermore, the expression of CD94/NKG2A in the immune cells and/or their ligand HLA-E in the tumor cells is also regulated by gut microbiota associated immune factors. These findings offer new insights for the clinical application of gut microbiota in precise and/or personalized treatments of tumors. In this review, we will discuss the impacts of GMMs and GMM educated immune cells on the activity of effective CD8 and NK cells and the expression of CD94/NKG2A in immune cells and/or their ligand HLA-E in tumor cells.